Description of the legal basis for the protection of labor rights of migrants - Serhii, Kozin; Tetiana, Tatarova; Taisiia, Korzh-Ikaieva; Olena, Sokurenko; Vitalii, Maltsev (Cuestiones Políticas, 2020)
The objective of the article under analysis is the legal framework for the protection of migrants' labour rights, identifying a specific range of category-related regulations and their main provisions. The theme of the study is the analysis of the legal basis for the protection of migrants' labour rights. The research methodology includes and agreed on the following general and special and legal methods: dialectical, logical, systematic, and legal, normative and canine, comparative and legal and legal method. The results of the study are identified by key regulations, including documents of international importance and the Ukrainian legal system, whose rules are dedicated to the regulation of social relations arising in the labour field of migrants. In terms of its practical implications, based on scientists' analyses, the focus is on the meaning of the term "migrant". An alternative definition is proposed. Finally, attention is paid to the declaratory nature of international law in the field of the protection of the labour rights of migrants and is part of the importance of acts of national law in regulating this matter.